THEORETICAL ASPECTS OF THE FORMATION OF FUNCTIONAL LITERACY OF SCHOOLCHILDREN - Batyrov, Zh. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
The article considers the issues of the formation of functional literacy of schoolchildren and ways of increasing students’ functional literacy that is seen as an indicator of mastering the competencies required in education. This article also discusses the current level of functional literacy of students and the causes and consequences of this issue. Also, this article analyzes domestic and foreign experience and conceptual ideas in the formation of functional literacy of students, which determines the practical and theoretical aspects of the study, and provides methodological recommendations. This article also discusses the results of international research conducted in the framework of TIMMS and the Student Assessment Program PISA in mathematics and science and identifies the factors that shape the functional literacy of students. In addition, a questionnaire was used to determine the role of mathematics teachers in the formation of functional literacy. When analyzing the answers to the questionnaire, several advantages and disadvantages were identified.
Keywords: functional literacy; skills; theoretical aspects; conceptual ideas; methodological ideas